Cyclonic wave in South China Sea - Day, Ching-her; Suphat Vongvisessomjai; I, Fude; Watanabe, Akira; Republic of China (Bangkok : Asian Institute of Technology, 1977)
Adequate knowledge of cyclonic waves is essential for design of coastal engineering work. In the absence of long recorded wave data in most situations, the only practical approach to obtain the required design criteria for wave will be wave hindcasting techniques. In wind wave hindcasting, the approach of Wilson's numerical method is used in general. But this appears tedious in preparing the wind field data involved, and more over, the approach is found to be suitable only for some specific cases. In this thesis, the procedure of Wilson's numerical method is heavily modified. The wind field, distance increment and time increment in each step of computation are the key variables modified in such a way that the model can be applied to compute the wave characteristics more efficiently. This modified model is then calibrated using data of two cyclones over Hong Kong and three cyclones over Taiwan at varying different geographies. The results established are quite promising; particularly when the wind data are reliable.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1978
Keywords: Ocean waves -- South China Sea